2004
DOI: 10.1128/aem.70.8.4642-4647.2004
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Chimeric Thermostable Pyrophosphatase To Facilitate Its Purification and Immobilization by Using the Choline-Binding Tag

Abstract: The thermophilic inorganic pyrophosphatase (Pyr) from Thermus thermophilus has been produced in Escherichia coli fused to the C terminus of the choline-binding tag (ChB tag) derived from the choline-binding domain (ChBD) of pneumococcal LytA autolysin. The chimeric ChBD-Pyr protein retains its thermostable activity and can be purified in a single step by DEAE-cellulose affinity chromatography. Pyr can be further released from the ChBD by thrombin, using the specific protease recognition site incorporated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Both PblA and PblB contain repeat regions of glycine‐tryptophan‐rich motifs, similar to the choline binding proteins of S. pneumoniae , and the lipoteichoic acid binding regions of InlB of Listeria monocytogenes (Jonquieres et al ., 1999). Moreover, we have shown that PblA and PblB can be purified from culture media by affinity chromatography with DEAE cellulose (a choline analogue), as has been done with other choline binding proteins (Sanchez‐Beato et al ., 1995; Caubin et al ., 2001; Fan et al ., 2004; Moldes et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both PblA and PblB contain repeat regions of glycine‐tryptophan‐rich motifs, similar to the choline binding proteins of S. pneumoniae , and the lipoteichoic acid binding regions of InlB of Listeria monocytogenes (Jonquieres et al ., 1999). Moreover, we have shown that PblA and PblB can be purified from culture media by affinity chromatography with DEAE cellulose (a choline analogue), as has been done with other choline binding proteins (Sanchez‐Beato et al ., 1995; Caubin et al ., 2001; Fan et al ., 2004; Moldes et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most popular domain is the poly-His tag, with high affinity for metal chelates (Figure 5) (e.g. for purification by IMAC) (Porath et al, 1975, Porath and Olin, 1983, Porath, 1992 but the range of these affinity peptides is huge and still growing: domains of affinity for cellulose, chitin binding domain, peptide tags, among 9 others (Arroyo et al, 2011, Bello-Gil et al, 2014, Bergeron et al, 2009, Bolivar and Nidetzky, 2012a, b, Cassimjee et al, 2011, Chern and Chao, 2005, Daunert et al, 2007, Kondo and Teshima, 1995, Kowsari et al, 2014, Kweon et al, 2005, Linder and Teeri, 1997, Martinez et al, 2000, Mateo et al, 2001b, Moldes et al, 2004a, Moldes et al, 2004b, Scaramozzino et al, 2005, Shpigel et al, 1999, Vishwanath et al, 1995, Wang et al, 2013a, Wiesbauer et al, 2011, Zhao et al, 2013. Table 1 shows a summary of the main domains used for this purpose while Table 2 shows some specific examples of uses of these domains.…”
Section: Coupled Immobilization/purification Of Enzymes and Proteins mentioning
confidence: 99%
“…In this sense, analysis of a collection of 21 mutated LytA NAM-amidases indicated that Ile-315, located in the last CBR, is a key amino acid residue in both enzymatic activity and folding (Romero et al 2007). Moreover, it is worth to mention that selective interaction of the CBM of LytA with choline or its analogs (tertiary or quaternary amines) has allowed its use as a tag to construct a variety of fusion proteins that may be purified using DEAE-cellulose, which acts as an affinity matrix for CBM-containing proteins (Sánchez-Puelles et al 1992, Moldes et al 2004. In this sense, a commercial kit based in this system is already available (C-LYTAG; http://www.biomedal.com).…”
Section: Choline and Cell Wall Hydrolasesmentioning
confidence: 99%